2020
DOI: 10.1186/s42466-020-00073-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and therapy of functional tremor a systematic review illustrated by a case report

Abstract: Background Diagnosis of functional movement disorders and specifically functional tremor (FT) (representing 50% of them) remains demanding. Additionally, due to heterogeneity of the disorders, structured concepts and guidelines for diagnosis and therapy are difficult to establish. Ascertaining the state of knowledge to derive instructions for operating procedures is the aim of this review. Main text Based on a standardized systematic literature res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
(54 reference statements)
0
3
0
2
Order By: Relevance
“…A revisão sistemática de Bartl et al (2020) 19 focada no tratamento de tremor funcional, descreve que, apesar de os estudos existentes serem ainda de pequena escala, estudos cegos têm apontado que a TCC deve ser o tratamento psicológico preferencial; outros métodos psicoterapêuticos não demonstraram o mesmo nível de evidência. Referem um ensaio controlado aleatorizado (ECA) de Espay et al (2019) 20…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A revisão sistemática de Bartl et al (2020) 19 focada no tratamento de tremor funcional, descreve que, apesar de os estudos existentes serem ainda de pequena escala, estudos cegos têm apontado que a TCC deve ser o tratamento psicológico preferencial; outros métodos psicoterapêuticos não demonstraram o mesmo nível de evidência. Referem um ensaio controlado aleatorizado (ECA) de Espay et al (2019) 20…”
Section: Resultsunclassified
“…Os estudos apresentam alguma evidência sobre a eficácia da TCC no tratamento de diferentes subtipos de SNF/D. No estudo de Bartl et al (2020) 19 sobre tratamento do tremor funcional, a TCC foi descrita como o tratamento psicológico preferencial, demonstrando redução significativa na severidade do tremor num ECA (Espay et al (2019)). 20 Para a tontura postural -perceptiva persistente, uma revisão sistemática (Trinidade et al (2018)) 21 sugeriu que a TCC, juntamente com outras abordagens multidisciplinares, como a reabilitação vestibular e inibidores da recaptação da serotonina e serotonina/noradrenalina, desempenha um papel importante no manejo desses casos.…”
Section: Discussionunclassified
“…The EEG preceding the movement artifact is averaged over multiple trials of self-initiated movements and BP is identified as a slow rise in the EEG that is seen prior to the movement onset. BP recorded before the EMG activity in patients with functional myoclonus is similar in appearance to that of normal voluntary movements [9]. It was Kornhuber and Deecke who described BP for the first time in 1964.…”
Section: Bereitschaftspotential (Bp)mentioning
confidence: 92%
“…Functional tremor (FT) is the most common form and represents about 50% of all FMDs [9]. FMDs are a great concern to the patient as it reduces the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have expressed different and sometimes directly opposite opinions on this issue. In particular, several publications indicate the possibility of the differential diagnosis of PD and ET by analyzing the phase difference in antagonist muscle EMG signals with high accuracy [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. However, other authors have discussed about the inapplicability of this approach to the differential diagnosis of PD and ET because it cannot provide acceptable accuracy [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%